School-based Hygiene Intervention to Prevent HelicObacter Pylori infection among childrEn (SHIP HOPE): protocol for a cluster-randomised controlled trial - Jing Qi; Yang Guo; Mengge Zhou; Feng Cheng; Yuhong Zeng; Yu'e Xi; Sitong Luo; Guanqi Zhao; Yamei Sun (BMJ Open, 2022)
Introduction Helicobacter pylori infection rates are high in China and worldwide, and maintaining good hygiene is effective in preventing H. pylori infection. Childhood is a critical stage for developing good hygiene practices. Therefore, in this study, we aimed to explore whether a comprehensive hygiene intervention can prevent H. pylori infection in primary schools in China.Methods and analysis The School-based Hygiene Intervention to Prevent HelicObacter Pylori infection among childrEn study is a cluster-randomised controlled trial, which will include approximately 2400 children in grades 2–4 from 60 classes in 10 primary schools of Linqu County, Shandong Province. Schools will be randomly assigned (1:1) via a computer-generated list, to receive either comprehensive hygiene intervention (intervention) or the usual health education lessons (control), with stratification by area (urban or rural). The interventions will include the following: (1) Children’s education: lessons and cartoon books designed to provide basic knowledge about hygiene, H. pylori, hand hygiene, diet and oral hygiene will be provided to children; (2) Caregiver’s education: children will be empowered to share hygiene-related knowledge with their caregivers as homework; caregivers will be also invited to the school for hygiene lessons; (3) School hygiene promotion: suggestions will be provided for improving the hygienic environment. Children in control schools will receive usual health education lessons according to the arrangements of each school. The primary outcome is the prevalence and incidence of H. pylori infection among children at 1-year follow-up. The secondary outcomes are H. pylori and hygiene knowledge, family eating customs and hygiene practices among children and their caregivers, as well as school absences owing to diarrhoea. Additionally, growth in children is set as an exploratory outcome. General linear mixed models will be used to analyse differences between the intervention and control schools.Ethics and dissemination Ethics approval has been obtained from the Institution Review Board of Tsinghua University (No: 20220020). Written informed consent will be obtained from each child and one of their caregivers. The findings of this study will be actively disseminated through scientific publications and conference presentations.Trial registration number ChiCTR2200056191.